Riks Analysis of Shallot Production Children’s Education Costs in Songan A Village, Kintamani Disdrict, Bangli Regency - Sarwa Adi Wisesa, I Made Pasek Anom (Suluh Pendidikan : Jurnal Ilmu-Ilmu Pendidikan, 2024)
Songan A Village is one of the villages that develop onion farming. Songan A village has farmer groups spread from the lowland to the highland areas. The problems faced are on the fluctuation of onion productivity which indicates that onion farming faces production risk. This study aimed to identify the types of risks and analyze the risk of onion production. This research used quantitative and qualitative analysis. The results showed that the types of production risks encountered in onion farming in the highland and lowland areas in the village of Songan A, namely climatic conditions, pest, and disease attacks. The risk of onion production in the highland areas (KV = 3.09) and lowland areas (KV = 2.46) was relatively high, where the level of risk of onion production in the highland areas was greater than that in the lower regions. This is due to the expected production, variant, and standard deviation of onion productivity in the highland areas is greater than that in the lower regions. The suggestion that can be given in this research is that farmers need to recognize the types of production risks faced in order to anticipate production decline